2023
DOI: 10.3390/plants12183285
|View full text |Cite
|
Sign up to set email alerts
|

Total Flavonoid Contents and the Expression of Flavonoid Biosynthetic Genes in Breadfruit (Artocarpus altilis) Scions Growing on Lakoocha (Artocarpus lakoocha) Rootstocks

Yuchan Zhou,
Steven J. R. Underhill

Abstract: Breadfruit (Artocarpus altilis) is a traditional fruit tree of 15–30 m height in the tropics. The presence of size-controlling rootstock in the species is not known. A small tropical tree species, lakoocha (Artocarpus lakoocha), was recently identified as a potential vigor-controlling rootstock, conferring over a 65% reduction in breadfruit tree height. To better understand the intriguing scion/rootstock interactions involved in dwarfing, we investigate flavonoid accumulation and its regulation in breadfruit s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…In the grafting technique, the substrate or matrix composition is important because it affects the hormonal crosstalk, protein and small-molecule movement, nutrient uptake, and transport in the grafted trees [ 1 ]. Meanwhile, it has also been found that Breadfruit ( Artocarpus altilis ) scions growing on Lakoocha ( Artocarpus lakoocha ) rootstocks enhance total flavonoid contents and the expression of flavonoid biosynthetic genes, such as AaCHS and AaDFR [ 11 ]. Cabernet Sauvignon grapes grafted on different rootstocks and rootstock combinations enhance saline–alkaline stress resistance capacity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the grafting technique, the substrate or matrix composition is important because it affects the hormonal crosstalk, protein and small-molecule movement, nutrient uptake, and transport in the grafted trees [ 1 ]. Meanwhile, it has also been found that Breadfruit ( Artocarpus altilis ) scions growing on Lakoocha ( Artocarpus lakoocha ) rootstocks enhance total flavonoid contents and the expression of flavonoid biosynthetic genes, such as AaCHS and AaDFR [ 11 ]. Cabernet Sauvignon grapes grafted on different rootstocks and rootstock combinations enhance saline–alkaline stress resistance capacity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%